2002
DOI: 10.1103/physrevb.66.094107
|View full text |Cite
|
Sign up to set email alerts
|

Structural transition in(C60)nclusters

Abstract: The structure of (C 60 ) n clusters (nϭ1-150) was investigated by heating them to definite temperatures in a helium bath ͑heating cell͒ with subsequent characterization in a time-of-flight mass spectrometer. The intensity anomalies in the resulting mass spectra reflect particularly stable configurations that resisted evaporation. However, the set of enhanced peaks ͑magic numbers͒ turned out to be temperature dependent. Clusters heated to a moderate temperature of 490 K yielded mass spectra indicating the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
51
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 65 publications
(138 reference statements)
7
51
0
Order By: Relevance
“…The balance between temperature and annealing time can be exploited to perform a wealth of new experiments probing the PES, as was demonstrated on large clusters of C 60 molecules. 12 It has previously been pointed out that experimentally observed magic peaks deviate from those predicted by electronic and geometrical shell filling arguments, and it has been suggested that entropy might be responsible for this. [17][18][19] Here, we present the first evidence from ab initio calculations that entropy is indeed important in determining absolute cluster stability.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The balance between temperature and annealing time can be exploited to perform a wealth of new experiments probing the PES, as was demonstrated on large clusters of C 60 molecules. 12 It has previously been pointed out that experimentally observed magic peaks deviate from those predicted by electronic and geometrical shell filling arguments, and it has been suggested that entropy might be responsible for this. [17][18][19] Here, we present the first evidence from ab initio calculations that entropy is indeed important in determining absolute cluster stability.…”
mentioning
confidence: 99%
“…Details of the experiment are published elsewhere. 12,15 Using this setup the thermal stability of small fullerene clusters was investigated. The peak intensity of ͑C 60 ͒ m clusters in the mass spectra was recorded in the temperature range between T = 150 K to 500 K ͑Ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, well-defined cluster temperatures are necessary for the determination of the heat capacity and melting point of free sodium clusters, [6][7][8] the activation energies and evaporation rate for the evaporation of weakly bound sodium clusters, 9,10 as well as the study of the decay behavior of fullerene dimers. 11,12 Mainly two approaches are commonly used to vary the cluster temperature experimentally. On the one hand, the cluster can be heated by the absorption of laser light.…”
Section: Introductionmentioning
confidence: 99%